The mesoamerican rain forest environmental history. livestock and landscape biodiversity at Los Tuxtlas, Mexico - Guevara S., S.; Laborde, J. (Pastos, 2014)
The current landscape of the Mesoamerican rain forest has been shaped by the migration of plant and animal species, natural events, and human intervention. This current reflection on the effects of livestock ranching in this region focuses on the impact to both the structure and the functioning of the landscape. Los Tuxtlas, Veracruz, Mexico, is both a case study and a reflection of the larger Mesoamerican landscape, where cattle livestock were first introduced in the 16th century and subsequently replaced with a new variety of cattle in the 19th century. Thus, Los Tuxtlas is an enclave of tropical rain forest in southeastern Mexico and illustrative of the environmental history of Mesoamerica as a whole, representing a landscape of flora and fauna that have resisted climatic changes, intense volcanic activity, and frequent hurricanes and tropical storms that have continuously occurred across time. More recently, human activities, such as hunting, gathering, and agriculture, have also formed the landscape beginning with the Olmecs, considered to be the mother culture of Mesoamerica. In the 16th century the European colonizers introduced on the northern tip of the volcanic range of San Martin in Los Tuxtlas several cattle varieties of Bos taurus, imported from the region of Guadalquivir, Spain. These cattle rapidly adapted tofree-range grazing, probably due to the absence of large native herbivores that had disappeared in Mesoamerica by the end of the Holocene, as well as due to the considerable extensions of secondary vegetation of abandoned agricultural fields, resulting from the disappearance of the indigenous farmers after the arrival of the Spanish. The cattle grazed on “grama” grasses, which proliferated during this time and emerged as part of the process of secondary succession, in addition to other plants and shrubs found within the rain forest. The livestock were adapted to this form of grazingfor over 500 years, dispersing trees and bushes and enriching the process of secondary succession. In the 20th century, Bos taurus was substituted for Bos indicus, a variety of cattle coming from Asia and raised only in pasturelands sown with African grasses, resulting in a lack of herbivorous activity compatible with the local ecosystems, as in the case of Bos taurus. A resulting defaunation and deterioration of the secondary vegetation has since occurred, and many “grama” grasses have since disappeared. In addition, the management practices associated with Bos indicus have stimulated an increase in deforestation and fragmentation of the rain forest, signifying a threat to regional biodiversity. However, numerous individuals and species of rain forest trees still persist in open fields across the landscape, mitigating, as they have throughout history, the impact of deforestation. The trees that are left behind are an element of the historical landscape management practices, implemented by the very first inhabitants of the region. These isolated trees form in many instances “living fences” that help to maintain the ecological connectivity between the remaining fragments of vegetation, in addition to sustaining processes of secondary succession and regeneration of the rain forest. The main objective of this essay is to demonstrate that by understanding the environmental history of the rain forest landscape of Mesoamerica, new possibilities may be presented for its design and management with the explicit goals of conserving biodiversity, preserving environmental services, and innovating productive and agricultural systems. Our objective is illuminated by examining historical landscape practices surrounding the introduction of cattle livestock in the region of Los Tuxtlas in southeastern Mexico and considering the relevance that they may hold for contemporary landscape management and the natural regeneration of the rain forest.